Respuesta :

Answer:

The equation of the line:

[tex]y+4x = 9[/tex]

At x = -1, the value of y = 13

At x = 0, the value of y = 9

At x = 3, the value of y = -3

Step-by-step explanation:

Given the equation

[tex]y+4x = 9[/tex]

solving for y

[tex]y+4x = 9[/tex]

subtracting 4x to both sides

[tex]y+4x-4x = 9-4x[/tex]

[tex]y = 9-4x[/tex]

Therefore, the value of y is:

[tex]y = 9-4x[/tex]

Now, solving x = -1, 0 and 3

substituting x = -1

[tex]y = 9-4x[/tex]

[tex]y = 9 - 4(-1)[/tex]

[tex]y = 9+4[/tex]

[tex]y = 13[/tex]

substitute x = 0

[tex]y = 9-4x[/tex]

[tex]y = 9 - 4(0)[/tex]

[tex]y = 9-0[/tex]

[tex]y = 9[/tex]

substitute x = 3

[tex]y = 9-4x[/tex]

[tex]y = 9-4(3)[/tex]

[tex]y = 9-12[/tex]

[tex]y = -3[/tex]

Therefore,

at x = -1, the value of y = 13

at x = 0, the value of y = 9

at x = 3, the value of y = -3

ACCESS MORE